2021
DOI: 10.1108/ijqrm-01-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting consumer purchase intentions of organic food through fuzzy AHP

Abstract: PurposeOrganic food market has grown rapidly on a global level and so is the interest of customers. The present paper ranks the factors and sub-criteria which are taken into consideration while making organic purchase decisions resulting in understanding the behaviour of consumers.Design/methodology/approachThe present paper considered a sample of 550 respondents in the area of Punjab. Fuzzy AHP technique was applied to understand the key factors and sub-criteria which play a major role in organic food purchas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 79 publications
5
14
0
1
Order By: Relevance
“…At the same time, consumer attitudes (H5) demonstrated a significant mediating effect on purchase intent. These findings are in synch with past literature showing a positive and mediating impact between attitude and purchase intention for organic products (Arora et al. , 2021; Matharu et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, consumer attitudes (H5) demonstrated a significant mediating effect on purchase intent. These findings are in synch with past literature showing a positive and mediating impact between attitude and purchase intention for organic products (Arora et al. , 2021; Matharu et al.…”
Section: Discussionsupporting
confidence: 91%
“…If there is a high level of PCE in a consumer, this should result in them having a favorable attitude toward organic products (Park, 2016). Arora et al (2021) studied the key factors which played a major role in organic food purchase decisions. The study found a significant impact of perceived consumer effectiveness on the trust, attitude and behavioral intentions of consumers ranked as per an order of preference while affecting the purchase intention of organic food.…”
Section: Scarcity Trust Attitude and Purchase Intentionmentioning
confidence: 99%
“…It is a personality trait that emerges from a person’s cost-benefit analysis of a particular outcome (Arora et al. , 2022) and is the crucial factor in determining a specific intention of behavior (Ajzen and Fishbein, 1980) or extends to which a person adopt favorable or unfavorable behavior in each situation (Ajzen, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social factors were measured with the support of mainly three items; consultation and reference of social network (family members, friends, supportive, etc), social status and information flow adopted by Nakalinda (2018) ;Tsakiridou et.al., (2008). Psychological factors are measured using six items; perception, motivation, happiness, enjoyment, and attitude adopted by Arora, Rani, Devi, and Gupta, (2022); Nakalinda (2018) ;Tsakiridou et.al., (2008). Each item was measured at an ordinal level with 7-point Likert scales such as 1 -Strongly disagree, 2 -Disagree, 3-somewhat disagree, 4-Neither agree nor disagree 5-somewhat agree, 6 -Agree, and 7 -Strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Not for show, but today people are moving to organic food to reduce the purchase of chemical residuals and consume nutritious food to maintain a high level of human health (Prada, Garrido, and Rodrigues, 2017). This rapid growth is occurring due to increased consumer confidence in organic foods as well as concern about possible health risks and environmental impacts of conventional food production methods (Arora, et al, 2022;Winter and Davis, 2006). The proportion of buying organic food has increased day by day and it is gratifying that, not only developed but also developing countries are turning to organic food consumption (Doan, 2021).…”
Section: Introductionmentioning
confidence: 99%